Safety and feasibility of laparoscopic reoperation for treatment of anastomotic leakage after laparoscopic colorectal cancer surgery. Issue 3 (11th January 2018) - Numata, Masakatsu; Yamaguchi, Tomohiro; Kinugasa, Yusuke; Shiomi, Akio; Kagawa, Hiroyasu; Yamakawa, Yushi; Furuatni, Akinobu; Manabe, Shoichi; Yamaoka, Yusuke; Torii, Kakeru; Kato, Shunichiro
Abstract: Introduction: The safety and feasibility of laparoscopic reoperation for anastomotic leakage remain unclear. Methods: A total of 3321 patients underwent laparoscopic surgery for primary colorectal cancer at a tertiary referral center from September 2002 to May 2016. Of these, 31 patients who underwent reoperation for treatment of anastomotic leakage were enrolled in this study and divided into two reoperation groups: laparoscopic ( n  = 15) and open ( n  = 16). Data regarding patient demographics, operative outcomes, morbidity, length of hospital stay, mortality, and stoma closure after reoperation in the two groups were compared. Results: No significant difference was observed in the primary surgery procedure between the two groups. Estimated blood loss (1 vs 9 mL, P  = 0.020), total postoperative complications (26.7% vs 68.8%, P  = 0.032), wound infection (0.0% vs 31.2%, P  = 0.043), and postoperative hospital stay (18 vs 31 days, P  = 0.017) were significantly better in the laparoscopic group than in the open group. Although the rate of stoma closure after reoperation was higher in the laparoscopic group, the difference was not significant (86.7% vs 62.5%, P  = 0.220). Conclusions: Laparoscopic reoperation exhibited better short‐term outcomes than open reoperation for selected patients with anastomotic leakage.